The impact of drought on U.S. hay prices - Rowley, Cordon Michael (Kansas State University, 2023)
The relationship between drought and hay prices has important implications for cattle producers and federal safety net programs. Cattle producers rely on forage through grazing pastureland or hay as a primary feed source. Climate change and increasing extreme weather events, including more widespread and persistent drought, threaten the viability of livestock production in several areas of the US. When drought reduces hay production, producers typically decrease their herd size to manage low hay supplies or higher hay prices. Several safety net programs make payouts designed to cover forage losses caused by lower-than-normal precipitation or extreme drought conditions. However, these programs may be less effective if hay prices are dramatically higher when payouts are made or if payouts are not strongly correlated with forage losses. While the relationship between hay prices and drought has been studied in Germany, contemporary research conducted with US data is limited. In this study, we analyze the relationship between monthly drought conditions and hay prices, at both the state and district (sub-state) levels. In addition to quantifying this relationship, we also explore whether the relationship between drought and hay prices has changed over time and space and the impact of local versus widespread drought. Methods We first use state-level monthly hay prices reported by USDA NASS, which is available from 1950 to present for alfalfa hay and from 1972 to present for non-alfalfa hay. We then regress monthly hay prices against drought levels, measured by Palmer Drought Severity Index (PDSI) and Drought Severity and Coverage Index (DSCI), with fixed effects for state, month, and year. Second, we conducted a novel exploratory analysis using hay prices reported at the district level from the USDA Agricultural Marketing Service (AMS), for 3 states. USDA AMS reports historic hay prices for districts within some U.S. states. We average county-level drought data at the AMS district level, with robustness checks for weighting based on cattle and hay production. We estimate a similar regression to our state-level model, and then extend it to include both district-level drought and state-level drought information. This allows us to consider whether regional market integration may mitigate the impact of local droughts. While drought conditions are arguably an exogenous shock to hay markets, our estimates are net effects of drought on hay price, that reflect how broad supply and demand factors respond to drought conditions. These factors, such as cattle inventories and local processing capacity, are excluded from our model due to simultaneity concerns. Results Using state-level data, we found that as both PDSI and DSCI increase, or drought becomes more severe, hay prices increase. Further, as drought becomes increasingly severe, the impact of drought on hay prices becomes greater. Mild drought conditions only have a small impact on hay prices, which could be due to production or management factors. These results are consistent when using growing-season precipitation instead of drought. For the district level, findings are consistent with state level analysis. Our results indicate the hay prices are not only strongly influenced by local drought, but also drought in proximate districts or states. The degree to which these effects are caused by hay markets, cattle inventories, or other market dynamics is an important topic for future research.
Keywords: Drought; Hay prices